PENERAPAN NILAI KEADILAN TERHADAP ANAK DALAM PERKARA TINDAK PIDANA NARKOTIKA (Studi Putusan Nomor: 9/Pid.Sus-Anak/2022/PN.Tar) - NI WAYAN ERNAWATI; ARIS IRAWAN; BASRI BASRI (Universitas Borneo Tarakan, 2025)
This study analyzes the application of justice values to children in narcotics crime cases based on Decision Number 9/Pid.Sus-Anak/2022/PN.Tar. The research background lies in the increasing involvement of children in narcotics offenses, as in the case where a child was instructed by his biological father to sell narcotics. This research employs a normative legal method with statutory and case approaches, drawing upon Law No. 35 of 2009 on Narcotics, Law No. 11 of 2012 on the Juvenile Criminal Justice System, and relevant court rulings. The findings show that the judge imposed a one-year imprisonment and two months of job training at the Probation Office (BAPAS) as a substitute for fines, considering both the juridical aspect under Article 114 paragraph (1) of the Narcotics Law and the sociological factor of parental influence. The study concludes that while the ruling complies with legal provisions, sociologically the child remains a victim whose rights are not fully protected. Therefore, strengthening the principles of diversion and restorative justice is essential to ensure that sentencing not only creates a deterrent effect but also safeguards the child’s future.